The Reconceptualizing Inclusive Pedagogy as an Alternative Learning Model in Schools: A Systematic Literature Review - Muhammad Syawaludin; Didi pramono; Muhammad Ilyas Marzuqi (Jurnal Profesi Keguruan, 2026)
Classroom instructional practices in schools remain dominated by standardized approaches that are insufficiently responsive to student diversity. This study aims to identify, synthesize, and formulate an alternative conceptual framework for inclusive pedagogy that is more adaptive to diverse learners. A qualitative meta-synthesis design was employed by reviewing relevant scholarly articles published between 2016 and 2026. Data were collected from Google Scholar and Scopus and analyzed using domain analysis to identify and synthesize key themes in inclusive pedagogy. The findings indicate that inclusive pedagogy is a multidimensional approach encompassing differentiated instruction, collaborative learning, student-centered approaches, Universal Design for Learning (UDL), supportive social relationships, and active, contextual learning. Based on these findings, this study proposes the CARE framework (Connect, Adapt, Respond, and Expand) as an alternative conceptual model that emphasizes meaningful connections, flexibility, responsiveness, and continuous improvement throughout the learning process. The proposed framework contributes to the development of more operational, inclusive learning models and provides practical guidance for teachers and policymakers in strengthening equitable, inclusive education in schools.